2008
DOI: 10.1088/0031-8949/77/06/065004
|View full text |Cite
|
Sign up to set email alerts
|

Accurate approximate solution to nonlinear oscillators in which the restoring force is inversely proportional to the dependent variable

Abstract: A modified generalized, rational harmonic balance method is used to construct approximate frequency-amplitude relations for a conservative nonlinear singular oscillator in which the restoring force is inversely proportional to the dependent variable. The procedure is used to solve the nonlinear differential equation approximately. The approximate frequency obtained using this procedure is more accurate than those obtained using other approximate methods and the discrepancy between the approximate frequency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The Fourier representation of (44) is given in (45). The following result was obtained by Beléndez et al [36] for the Fourier coefficients a 2n+1 :…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The Fourier representation of (44) is given in (45). The following result was obtained by Beléndez et al [36] for the Fourier coefficients a 2n+1 :…”
Section: Resultsmentioning
confidence: 60%
“…The main purpose of this paper is to construct an analytical approximation to the solution of (1) using a modified RHBM introduced by Beléndez et al [36,37] and which has been applied for truly conservative nonlinear oscillators with good results. To solve (1) by the modified RHBM, a new independent variable τ = ω t is introduced.…”
Section: Solution Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for large x, the equation of motion is that of a truly nonlinear oscillator in which the restoring force is inversely proportional to the dependent variable and   2 / 2 A  1.25331/ A [20][21][22], which tends to zero when A decreases. Consequently the angular frequency  increases from 1 to 1.25331/A as the initial value of x(0) = A increases.…”
Section: Formulation and Solution Methodsmentioning
confidence: 99%
“…The most commons and most widely studied methods of all approximation methods for nonlinear differential equations are perturbation methods [1]. Some of other techniques include variational and variational iteration methods [4][5][6][7][8][9][10][11][12], exp-function [13,14], homotopy perturbation [15][16][17][18][19][20][21][22], equivalent linearization [23,24], standard and modified Lindstedt-Poincaré [25][26][27][28][29], artificial parameter [30,31], parameter expanding [32][33][34], harmonic balance methods [1,[35][36][37][38][39][40], etc. Surveys of the literature with numerous references and useful bibliography and a review of these methods can be found in detail in [28] and [41].…”
Section: Introductionmentioning
confidence: 99%